HUBUNGAN KEBIASAAN MENGGOSOK GIGI DAN KONSUMSI MAKANAN JAJANAN KARIOGENIK DENGAN KEJADIAN KARIES GIGI PADA ANAK USIA PRASEKOLAH DI TAMAN KANAK-KANAK PONDOK BERINGIN SEMARANG - Wahyuningsih dan Sri Hastuti, Maulidta KW, (STIKES Widya Husada Semarang, 2010)
The Correlation Between Habit of Tooth Cleaning and Cariogenic Food Consumption With the Dental Caries Incident of Pre School Children at the Kindergarten Pondok Beringin Semarang Oleh Ns. Maulidta K W, Ns. Wahyuningsih, dan. Sri Hastuti AKPER Widya Husada SemarangA dental caries is disease of dental hard tissue signed with the incident of demineralization of an organic part and dissolving of orgaic subtance. The prevalence of dental caries in child which is still high is due to habit of tooth cleaning and Cariogenic Food preference. The research aims are the know to correlation between habit of tooth cleaning and cariogenic food consumption with the dental caries incident of preschool children at the kindergarten Pondok Beringin Semarang. This research used quantitative non eksperimental research method with correlation study. Data had been collected by questioner and observation of tooth. It used total sampling were 69 children. Data was analyzed with chi square test. The result indicates that habit of tooth cleaning of 40% in less category, cariogenic food preference was in high category of 88,3 %, and caries prevalence in the amount of 85% mean while from treatment ofmouth cleanliness, it was known that 41,67 % in less category. The result of statistical test indicates that there is significant correlation between habit of tooth cleaning (p=0,035) and cariogenic food preference(p=0,007) with the incident of dental caries, and most influence factor is cariogenic food consumption (exp(B)=5,731). Decreasing of restricting cariogenic food as one of efforts to prevent dental caries. Keywords : dental caries,cleaning tooth,cariogenic,pre school children